Exhibition of antifungal resistance by sterol-auxotrophic strains of Candida glabrata with intact virulence. Issue 1 (7th March 2022) - Nagi, Minoru; Tanabe, Koichi; Tanaka, Kazuko; Ueno, Keigo; Nakayama, Hironobu; Ishikawa, Jun; Abe, Masahiro; Yamagoe, Satoshi; Umeyama, Takashi; Nakamura, Shigeki; Sugai, Motoyuki; Hazen, Kevin C.; et al.
Abstract: Background: Candida glabrata is an emerging fungal pathogen in immune-compromised hosts. Previously undetected C. glabrata isolates were successfully recovered from clinical specimens by adding sterols to the growth medium. The clinical isolates are unable to synthesize ergosterol but can take up exogenous sterols under aerobic conditions. Objectives: This study characterizes the sterol-auxotrophic C. glabrata strains, examines the mutation(s) in sterol synthesis genes, characterizes the drug susceptibility and evaluates the virulence in a mouse infection model. Methods: Drug susceptibility of the C. glabrata strains was evaluated in a sterol-supplemented medium. The coding sequences of the sterol synthesis genes were analysed in six sterol-auxotrophic strains of C. glabrata . The fungal burden of mice infected with C. glabrata strain was determined. Results: The sterol-auxotrophic strains showed high-level resistance to both azoles and amphotericin B when sterols were supplied in the test medium. Additionally, the strains harbour missense mutations in either ERG1 or ERG7 . Significant differences in fungal burden were not observed between the sterol-auxotrophic strain and the sterol-competent strain with the mice infection models. Conclusions: The sterol-auxotrophic C. glabrata strain investigated in this study seemed to maintain intact virulence, probably due to the supply of exogenous sterols from host organ(s). This suggests that exogenous sterol uptake develops antifungal resistance during infection.